(untitled) (Fiep Bulletin - online, 2017)
Power, coupled with anaerobic energy sources, is one of the most important components of sports performance.However, it should not be seen as an isolated capability. In combination with a high standard of technical and coordinationmovements, with the specificity of sport or discipline, the various manifestations of physical ability, speed is of prime importancefor success in individual or collective sports. Anaerobic power is a component present in the stimulus generated by the demandsof the modality. Anaerobic power is understood to be the greatest effort made during a given action by the shortest unit of timeavailable. This physical ability is present at the crucial and decisive moments of the game. The anaerobic lactic power is themaximum frequency of energy production during a maximum effort with production of glycolytic energy and the anaerobic poweris the maximum frequency (quantity per unit time) with which energy can be produced by the system, the methodology was (9minutes). From the data collected, the test results point to a significant difference for op = 0.0004 after 10 months of training, thusshowing an improvement in anaerobic power. The functional evaluation of adolescents in the sports improvement phase pointsout clear and objective information, which serves to deepen the training process and effectiveness of the work developed.Despite the advances of globalization, and technological influence both in daily life and in the elaboration of sophisticatedtraining, it is noticed that there are still many effective training methods through sports training, it is believed that subjectingadolescents to the maximum level of training can lead to Young person to accumulate blood lactate. Given the results obtained,we perceive the need and importance of training through sports practice, since these activities work in the motivation andpleasure of the execution. It is concluded that progressive intervention programs, through sports in schools, regardless ofmodality contributes significantly In the development of adolescent aerobic power.